Slowed articulation rate is associated with information processing speed decline in multiple sclerosis: A pilot study - Friedova, Lucie; Rusz, Jan; Motyl, Jiri; Srpova, Barbora; Vodehnalova, Karolina; Andelova, Michaela; Novotna, Klara; Novotny, Michal; Ruzickova, Hana; Tykalova, Tereza; Kubala Havrdova, Eva; Horakova, Dana; et al. (Journal of clinical neuroscience, 2019)
BACKGROUND: Impairment of cognition and speech are common in multiple sclerosis (MS) patients, but their relationship is not well understood. OBJECTIVE: To describe the relationship between articulation rate characteristics and processing speed and to investigate the potential role of objective speech analysis for the detection of cognitive decline in MS. METHODS: A total of 122 patients with clinically definite MS were included in this cross-sectional pilot study. Patients underwent three speaking tasks (oral diadochokinesis, reading text and monologue) and assessment of processing speed (Symbol Digit Modalities Test [SDMT], Paced Auditory Serial Addition Test-3 s [PASAT-3]). Association between articulation rate and cognition was analyzed using linear regression analysis. We estimated the area under the receiver operating characteristics curves (AUC) to evaluate the predictive accuracy of articulation rate measures for the detection of abnormal processing speed. RESULTS: We observed an association between articulation rate and cognitive measures (rho = 0.45-0.58; p < 0.001). Faster reading speed by one word per second was associated with an 18.7 point (95% confidence interval [CI] 14.9-22.5) increase of the SDMT score and 14.7 (95% CI 8.9-20.4) point increase of PASAT-3 score (both p < 0.001). AUC values of articulation rate characteristics for the identification of processing speed impairment ranged between 0.67 and 0.79. Using a cutoff of 3.10 in reading speed, we were able to identify impairment in both the SDMT and PASAT-3 with 91% sensitivity and 54% specificity. CONCLUSION: Slowed articulation rate is strongly associated with processing speed decline. Objective quantitative speech analysis identified patients with abnormal cognitive performance.
Keywords: ROC Curve; Humans; lidé středního věku; Multiple Sclerosis; Dysarthria; Female; dospělí; Speech; dysartrie; lidé; Regression Analysis; pilotní projekty; Pilot Projects; Adult; Multiple sclerosis; Cognition Disorders; Information processing; ženské pohlaví; roztroušená skleróza; Male; Middle Aged; Articulation; Cross-Sectional Studies; kognitivní poruchy; ROC křivka; mužské pohlaví; Cognition; průřezové studie; regresní analýza